Autism in regional and remote communities: Examining the effect of an autism spectrum disorder diagnosis on regional and remote families and innovative therapies - Parsons, David Norman (Curtin University, 2019)
This PhD project aims to address therapy service access barriers for families of children with autism spectrum disorder living in regional and remote Western Australia. Therefore the feasibility, effectiveness and appropriateness of an information communication technology based intervention, the Therapy Outcomes By Your Playpad Application were examined. The findings provide partial support for the Therapy Outcomes By Your Playpad Application as a feasible, effective and appropriate intervention for families of children with autism spectrum disorder.